RESULTS OF THE UNIFIED STATE EXAM: EXPERIENCE OF INTERREGIONAL COMPARISONS - Liutsiya M. Nurieva; Sergey G. Kiselev (Obrazovanie i Nauka, 2017)
Abstract. The aim of the presented article is the search for the factors that determine the results of the Unified State Exam (USE) in the Russian regions through the example of mathematics exam in 2013.Methods. During the study of the exam results the authors applied the methodology of complex research, including methods of comparative and statistical analysis of published data on the results of the exam by Federal Center of Testing and Federal Institute for Education Measurement.Results and scientific novelty. It was found that the exam results in the region depend not only on the level of students’ training, but on the quality of test materials and the discipline of the test procedures.Practical significance. The authors suggest that the findings of this study will contribute to the improvement of techniques and technologies of the exam.